EVALUASI PROGRAM EKSTRAKURIKULER TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DI SD NEGERI PADAAN 02 - Rizki Darmawan; Agustina Tyas Asri Hardini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The mastery of information and communication technology has become a crucial need in the era of globalization. This study aims to evaluate the extracurricular program of information and communication technology at SD Negeri Padaan 02. The research used a qualitative approach with the CIPP evaluation model covering aspects of context, input, process, and product. Data collection techniques included interviews, observations, and document studies, while data analysis was conducted through data reduction, data presentation, triangulation, and conclusion drawing. The results showed that the program was designed according to the needs of students and the school’s vision, supported by adequate facilities and human resources despite some technical obstacles. The implementation process was effective, and the program outcomes indicated an improvement in students’ technological skills. This study concludes that the extracurricular information and communication technology program at SD Negeri Padaan 02 successfully achieved its goals, with recommendations to enhance facilities maintenance and activity documentation.